De regio als bestuurlijk schaalniveau - Hooge, Edith (2022)
This diptych is the result of the first subproject of the study 'Steering with Space' on regional steering networks in education. In the first subproject of this study, we investigated what is meant by "the region", how the region can be conceptually, what "the region" means as an administrative scale level and how the government can use it to can steer with it. For this purpose, we did two things: firstly, we conducted a systematic international literature study and Firstly, we conducted a systematic international literature study and secondly, we analysed the government's policy discourse on the region. Secondly, we analysed the government's policy discourse on 'the region in Dutch education'. In both the literature study and the policy analysis, we proceeded openly and inductively by examining the sources - scientific (research) literature and policy documents, respectively - by allowing them to "speak for themselves" as much as possible. We did this by systematically searching for and selecting the sources, mapping their contents, ordering them, and then arriving at findings.